Late results after subtrochanteric angulation osteotomy in young patients - Schiltenwolf, Marcus; Carstens, Claus; Bernd, Ludger; Lukoschek, Martin (Journal of pediatric orthopaedics, 1996)
Young patients with painful congenital dislocation of the hips need surgery if conservative treatment is unsuccessful. A total of 24 patients after 28 subtrochanteric angulation osteotomies without resection of the femoral head were followed up (mean, 17 years) to evaluate long-term results. Most patients maintain improved function: 20 hips showed persistent gain of abduction, 14 patients showed improvement of gait, and 18 patients described less pain. The degree of angulation must equal the inclination of the pelvic wall to influence hip stability as well as hip range of motion. Osseous reactions of support-seen in 10 hips-are not proof of operative success. Angulation osteotomy does not exclude later surgical procedures such as total hip replacement.